PREVALENCE AND CAUSE OF CHILDHOOD BLINDNESS: A SYSTEMATIC REVIEW - Nur Karim, Akbal; Santosa, Agung (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Childhood blindness is defined as a group of eye diseases occurring in childhood or early adolescence. Good parental knowledge of childhood blindness is important for early detection and management of the lifelong burden. The aim: This study aims to provide an explanation and prevent children with blindness and visual impairment Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 until 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 1751 articles, whereas the results of our search on SagePub brought up 120 articles. The results of the search conducted for the last year of 2013 yielded a total 11 articles for PubMed and 8 articles for SagePub. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: The causes of childhood blindness from the available blind school studies revealed that causes of childhood blindness have mainly shifted from corneal causes to whole globe abnormalities.